News coverage of ocean issues and its impacts on public perceptions and conservation information‐seeking of sea turtles. Issue 4 (15th February 2022) - Santos, Bianca S.; Wong‐Parodi, Gabrielle
Abstract: The news media can influence how the public learns about environmental issues, including endangered marine species such as sea turtles, which may prompt further information‐seeking. However, what people learn through the media can be problematic for conservation efforts if it is misaligned with scientific priorities. Here, we seek to better understand how members of the public learn about sea turtles through the news, assess public perceptions and knowledge about these animals, and evaluate how these variables are associated with information‐seeking behavior on their conservation. We surveyed a representative sample of 1162 adults living in the coastal United States and collected information on ocean news consumption, sea turtle interest, risk perceptions of sea turtle population status and individual threat types, self‐reported knowledge, and information‐seeking behavior. News consumption was associated with interest, risk perceptions of population status, and self‐reported knowledge about sea turtles. Although news consumption was not associated with risk perception about individual hazards, individuals generally viewed pollution as a top hazard facing sea turtle populations, which may misalign with scientific understanding. Greater interest, risk perceptions of population status and overall threat, and knowledge was associated with more information‐seeking behavior, with knowledge moderating the relationship between risk perceptions of population status and information‐seeking behavior. These findings improve understanding of how the public learns about sea turtles through the news media, suggests coupling messaging about sea turtles with their risks may provide more effective conservation messaging, and highlights how educators and conservation stakeholders can use the news as a communication tool. Abstract : The objective of this study was to better understand how members of the public learn about sea turtles through the news, assess public perceptions and knowledge about these animals, and evaluate how these variables may be associated with information‐seeking behavior on their conservation. Through a national survey of U.S. coastal residents, we found that ocean news consumption was associated with interest, risk perceptions, and knowledge about sea turtles and their conservation, which were ultimately associated with more information‐seeking behavior. We also found that the U.S. public believes pollution to be the most significant threat impacting sea turtle populations, which may misalign with scientific understanding and perhaps be exacerbated by the widespread attention on sea turtles as a marketing icon for the anti‐plastics movement.